Cover Jurnal Media Teknik Sipil, Vol.12, No.1, Februari 2014 - Cover . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2014)
Cover Jurnal Media Teknik Sipil, Vol.12, No.1, Februari 2014